PENGARUH PENGALAMAN, KEAHLIAN, SITUASI AUDIT, ETIKA, DAN GENDER TERHADAP KETEPATAN PEMBERIAN OPINI AUDITOR MELALUI SKEPTISISME PROFESIONAL AUDITOR - Sutrisno Sutrisno; Diana Fajarwati (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2014)
The purpose of this study is to provide empirical evidence of how much direct influence between the experience,expertise, audit situation, ethics, and gender of the accuracy of the provision of the auditor's opinion as well asindirect influence between the experience, expertise audit situations, ethics and gender of the accuracy of theprovision of the auditor's opinion through skepticism professional auditor as an intervening variable. This researchuses descriptive method, with questionnaire as a tool to collect data. This research disclosed that experience, theaudit situation, ethics and gender does not have a significant positive effect to the accuracy of the auditor's opinion,while expertise has significant positive effect to the precision of the auditor's opinion, and experience, expertise,ethics, gender was not a significant positive effect on the accuracy of the provision of the auditor's opinion by theauditor's professional skepticism positive effect while the audit situation and significant precision giving theauditor's opinion by the auditor's professional skepticism